Effect of Aflatoxin-B1 Exposure on Performance and Haematoogical Stress Indicators in Male Sprague Dawley Rats - A. B. Sikiru; S. S. A Egena; I. C. Alemede; J. O. Alabi; J. O. Makinde; H. Bebera (Fountain Journal of Natural and Applied Sciences (FUJNAS), 2024)
Aflatoxin-B1 is a ubiquitous mycotoxin usually accumulated in food and feeds, thereby posing a critical health risk to humans and animals. This study was carried out to determine its effects on performance characteristics and haematoogy indicators of stress in male Sprague Dawley rats. The rats were randomly distributed into 4 groups (n=10 per group) including an unexposed group that served as control and other groups which were orally exposed to 150 µg of aflatoxin-B1 per kg body weight on a varied basis for 28 days. The records of food intake and body weight changes were obtained while blood was collected at the end of the study for downstream analyses. There was a significant difference observed in food intake, body weight, kidney weight, liver weight, lung weight, and testes weight of the rats (p<0.05). There was a significant difference observed in the heterophil-lymphocytes ratio and bilirubin concentration as haematology biomarkers of stress in the rats (p<0.001). The study concluded that aflatoxin-B1 exposure in rats is capable of inducing stress-related performance dysfunction such as reduced food intake and body weight loss, while haematoogy biomarkers of stress heterophil-lymphocyte ratio and bilirubin concentrations could be used as potential biomarkers suitable for measuring these performance dysfunctions. There is a need for further studies to establish the possible use of heterophil-lymphocyte ratio and bilirubin as measures of performance compromise in response to aflatoxin-B1 exposure in rats.